The Empirical Study on Alternative Assessment of Portfolio Based on Saaty's Analytic Hierarchy Process (AHP) - Cheng, Sheila; Siow, Heng Loke (2019)
Purpose - Digital knowledge has been recognised as an indispensable asset in today’s world. As an educator, how can we help students to acquire the 21st century skills? Digital learning technology plays an important role in the assessment. A variety of assessment formats has been recommended to engage and motivate students’ learning. Portfolio / e-portfolio has been recommended by many studies (UNSW, 2019; Kampylis, Punie& Devine, 2015; McDonald, 2011) as one of the effective ways to document and communicate students’ learning process. However, the portfolio is a very subjective form of assessment. This paper attempts to conduct an empirical study on alternative assessment of portfolio based on Saaty’sAnalytic Hierarchy Process (AHP). The assessment framework called “3AHP” is established against the course learning outcomes (CLOs). Approach - Two sets of portfolios submitted by undergraduate students for two different courses applying for course exemption through Accreditation of Prior Experiential Learning (APEL) were assessed respectively by both the traditional way of rating scales with rubrics and 3AHP. A comparison of both rating scale assessment versus 3AHP is discussed. Assessment criteria for both rating scales and 3AHP are discussed. Findings - Results of this study indicate that both rating scales and 3AHP generate similar assessment results. Implications - 3AHP assessment approach simplifies the portfolio assessment processes. In addition, 3AHP approach standardizes and minimizes the variation in portfolio assessment among different assessors. 3AHP assessment approach is generic in nature. It can be applied to assess the portfolio of formal, informal and non-formal learning. It can also be implemented in different disciplines and to simplify the task of assessors at institutions of higher learning.